Prevalence of diabetes in Malaysia and usefulness of HbA1c as a diagnostic criterion. Issue 7 (23rd March 2013) - Wan Nazaimoon, W. M.; Md Isa, S. H.; Wan Mohamad, W. B.; Khir, A. S.; Kamaruddin, N. A.; Kamarul, I. M.; Mustafa, N.; Ismail, I. S.; Ali, O.; Khalid, B. A. K.
Abstract Aim The prevalence of diabetes mellitus among Malaysians aged ≥ 30 years of age has increased by more than twofold over a 20‐year period. This study aimed to determine the current status and to evaluate the diagnostic usefulness of the HbA1c cut‐off point of 48 mmol/mol (6.5%). Methods Using a two‐stage stratified sampling design, participants aged ≥ 18 years were recruited from five zones selected to represent Malaysia. An oral glucose tolerance test was performed on all those not known to have diabetes. Results A total of 4341 subjects were recruited. By World Health Organization criteria, the prevalence of diabetes mellitus was 22.9%; of that percentage, 10.8% was known diabetes and 12.1% was newly diagnosed diabetes. Diabetes was most prevalent amongst Indians (37.9%) and Malays (23.8%). Prevalence of new diabetes mellitus was only 5.5% (95% CI 4.9–6.3) when based on the HbA1c diagnostic criteria of 48 mmol/mol (6.5%) and, although the cut‐off point was highly specific (98.1%), it was less sensitive (36.7%) compared with 45 mmol/mol (6.3%), which showed the optimal sum of sensitivity (42.5%) and specificity (97.4%) in identifying new diabetes mellitus. Conclusion This study recorded an overall diabetes prevalence of 22.6%, almost a twofold increase from 11.6% reported in 2006. This was likely attributable to the higher prevalence of new diabetes (12.1%) diagnosed following an oral glucose tolerance test. An HbA1c of 45 mmol/mol (6.3%) was found to be a better predictive cut‐off point for detecting new diabetes in our multi‐ethnic population.